KEANEKARAGAMAN TUMBUHAN VEGETASI HUTAN MANGROVE DI TUMBU-TUMBU, LAMPEAPI DAN WUNGKOLO, PULAU WAWONII, SULAWESI TENGGARA - Suhardjono Suhardjono (Research Center for Biology-Indonesian Institute of Sciences, 2012)
Fifty four species belong to 32 families and 46 genera were recorded in mangrove areas of Tumbu-tumbu, Lampeapi and Wungkolo(Wawonii Island, South East Sulawesi). Twenty four of them included in the IUCN (Anonim, 1997) list. The richest species diversity found in Lampeapi (48 species) followed by Tumbu-tumbu (39 spesies) and Wungkolo (29 species).The dominant species of those areas were Rhizophora apiculata, R. mucronata and Bruguiera gymnorrhiza.The total average density of three was 268–742 individu/ha, with basal area 16.14–28.99 m 2/ha, sapling plant was 66–317 indv./ha will basal area 0.38–0.92 m /ha and seedling plant was 88,13 –146,66 individu/ ha.